Tapestry : Listening & Speaking 2 - Mary McVey Gill, Pamella Hartmann (Heinle & Heinle, 2000)
Designed for use in Arab and Islamic cultures, Tapestry Middle East Edition is the ideal choice for culturally appropriate English language instruction.